Environmental Legal Aspects In Protection Of Natural Resource Management - Rusdin Alauddin (LEGAL BRIEF, 2022)
This study aims to identify the application of Administrative, Civil and Criminal sanctions against Environmental Criminals and formulate factors that affect law enforcement against environmental criminals, in the context of utilizing/protecting natural resources. The type of research used in this research is normative legal research, there are 3 kinds of library materials used, namely primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques used through documentation studies or through literature searches. The data obtained from the literature study will be analyzed with descriptive analysis techniques. The results of the study obtained that the application of sanctions from the aspect of environmental law to the use of Natural Resources was carried out through three fields, namely the field of State Administration, the field of Civil and the field of Criminal Affairs. The application of sanctions in these three fields is still very minimal contribution in efforts to protect and manage the environment in Indonesia. Many factors are obstacles to the application of legal sanctions in the environmental sector, including: Legislation in the field of environment still has many shortcomings. Among other things, the incompleteness of formal legal and material law issues contained in the PPLH Law. These deficiencies are often used to avoid sanctions by environmental crimes, law enforcement factors that have shortcomings in terms of quality and quantity. This is illustrated in many cases, especially in major cases such as the Lapindo Mud Case, factors of very inadequate supporting facilities, Factors it seems that the level of awareness, compliance and behavior of citizens towards laws and regulations is still very low